Human health risk assessment of toxic heavy metal and metalloid intake via consumption of red swamp crayfish (Procambarus clarkii) from rice-crayfish co-culture fields in China. (October 2021) - Tan, Yunfei; Peng, Bo; Wu, Yinglin; Xiong, Lijing; Sun, Junxiao; Peng, Guohui; Bai, Xufeng
Abstract: The food safety of a popular aquatic product, red swamp crayfish ( Procambarus clarkii ), has caused widespread public concern. Rice-crayfish mixed farming currently takes advantage of crayfish production and is becoming the dominant farming method. It is still unknown whether this new aquaculture model produces crayfish with safe accumulated doses of toxic heavy metals and metalloids. In the current study, eleven farms in the Hubei and Hunan provinces, which account for more than 60% of the crayfish production in China, were selected to sample crayfish and their culture environment background (sediment and water), and determine their As, Cr, Cd, and Pb levels. The estimated daily intake (EDI) risk model was used to evaluate the human health risk of consuming crayfish. The concentrations of the four toxic elements were lower in the abdominal muscle than in the exoskeleton and hepatopancreas that is not suggested to be consumed. As the edible part, abdominal muscle did not exceed the national safety threshold for toxic elements. The geographic environmental background had little impact on the accumulation of toxic elements in the abdominal muscle of crayfish. The EDI results suggest that neither children nor adults exceed the provisional tolerable daily intake threshold, and the target hazard quotient (THQ) and cancer health risk (CR) for both children and adults were less than 0.12 and 1.5 × 10 −9, respectively, which are far less than the thresholds (THQ < 1 and CR < 10 −6 ). Furthermore, 139 and 488 kg crayfish were the critical values for the annual consumption by children (20 kg) and adults (70 kg), respectively. Highlights: It is not suggested to consume hepatopancreas of crayfish for human. Arsenic accumulates more than Cd, Cr, and Pb in the abdominal muscle of crayfish. There is a low or no health risk for consumption of abdominal muscle of crayfish. The critical value of crayfish consumption by children (20 kg) is 139 kg/year. The critical value of crayfish consumption by adults (70 kg) is 488 kg/year.